The gender gap in Italian academic medicine from 2005 to 2015: still a glass ceiling: Gender gap - Larese Filon, Francesca; Paniz, Erica; Prodi, Andrea (La Medicina del Lavoro, 2019)
Background: Although women make up half of the population of medical students and residents, they are still under-represented in prominent leadership positions in academia. The disparity is greatest at the highest levels and represents a loss of talent for academic health centers, showing that women must choose between career advancement and personal life. Objectives: The aim of this study was to analyze gender distribution in Italian medical academia in all hierarchical roles (researchers in tenure track positions, associate and full professors) in different disciplinary scientific fields (SSD) in 2015 compared to 2005. Methods: Medical faculties were considered at 31/12/2005 and 30/09/2015, and analyzed using Excel data sheet (Office for Windows 2007). Database was analyzed using STATA software (Texas, Inc. 2014). Results: Women are under-represented in all careers: in 2005 they made up 36.2% of researchers, 21.7% of associate professors and only 9.4% of full professors. The percentage of women researchers increased significantly (p<0.0001) in 2015 to 41.9%, but the percentages of female associate professors (25.3%) and full professors (14.2%) were still extremely low. Discussion: Our study shows that women are under-represented in Italian academia, with only a slight increase in presence in 2015 compared to ten years before. More action is needed to create a supportive environment, increase awareness and monitor potential discrimination.